1995
DOI: 10.1111/j.1464-410x.1995.tb07580.x
|View full text |Cite
|
Sign up to set email alerts
|

Maximum and average urine flow rates in normal children‐the Miskolc nomograms

Abstract: Objective To establish normal reference ranges of urinary flow rates in children. Subjects and methods From a screening programme, 200 healthy children (96 girls and 104 boys, between 3 and 18 years old) with no renal, urological, psychological or neurological disorders were selected, and they provided 433 micturitions for analysis. The children were divided into those with body surface areas of <0.92 m2, between 0.92 and 1.42 m2 and > 1.42 m2. The voided volume, maximum and average flow rates of urine were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 18 publications
1
43
1
1
Order By: Relevance
“…This is interpretable by the girl's shorter urethra. The mean maximum urine flow rates (19.9 ml/sec for boys and 23.5 ml/sec for girls) were found to be lower in this study than those reported in western studies (Miskole [10]: Mean maximum urine flow rate 14 ml/sec for boys and 16 ml/sec for girls). This may be explained to some extent by the fact that because of religious considerations children have very early toilet training and parents force them to void every 1–2 hours in the toilet-training period to avoid wetting.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…This is interpretable by the girl's shorter urethra. The mean maximum urine flow rates (19.9 ml/sec for boys and 23.5 ml/sec for girls) were found to be lower in this study than those reported in western studies (Miskole [10]: Mean maximum urine flow rate 14 ml/sec for boys and 16 ml/sec for girls). This may be explained to some extent by the fact that because of religious considerations children have very early toilet training and parents force them to void every 1–2 hours in the toilet-training period to avoid wetting.…”
Section: Discussioncontrasting
confidence: 79%
“…Miskole [10] nomogram noted that the curves of 50% of the average and maximum flow rates were the same in both sexes when the voided volume was less than100 ml. But when the voided volume is more than 100 ml, the curves for the girls were higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-seven patients without CAD were included in Group B. They had a shorter duration of diabetes and good metabolic control (mean fructosamin level was 2.9 AE 0.6 mmol/L, Table I), and their mean voided volume was 258 AE 52 mils at ¢rst sensation of bladder fullness.The controls for Group Awere obtained from a previous uro£ow screening study, where 231 healthy children voided at ¢rst and at maximal sensation of bladder fullness [Szabo and Fegyverneki, 1995]. Twenty healthy children voided 488 AE 94 mils and formed control for Group A, and another 30 healthy children voided 260 AE 50 mils and formed control for Group B.…”
Section: Methodsmentioning
confidence: 99%
“…However, the regression method used standard errors to predict the values of the percentiles that may not apply well in skewed data. Such error may explain the unreasonable findings in the most commonly adopted Miskolc nomograms : the line of 5th percentile of the Q max in boys aged 3–7 years was higher than those of children aged 8–13 years. As the number of participants was larger in the present study, we used the ranking method to plot the real percentiles on the nomogram.…”
Section: Discussionmentioning
confidence: 98%